IMPLEMENTASI PROGRAM PEMBERDAYAAN DAN PENINGKATAN KELUARGA SEJAHTERA KABUPATEN PONOROGO - Norrahmawati, Dinda; Hayu Dwimawanti, Ida; Puspo Priyadi, Budi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The implementation of the empowerment and increase in family prosperity program shows the implementation of the Strategic Plan document for the Population Control and Family Planning Service for 2021-2026. This research aims to analyze the implementation of the empowerment program and increase prosperous families and find the inhibiting factors for the empowerment program and increase family prosperity in Ponorogo Regency as seen through the implementation theory put forward by Van Meter and Van Horn. Ponorogo Regency was chosen based on its achievements in family planning villages in East Java, but in its implementation the program activity did not show compliance with applicable regulations. The method used in this research is qualitative research with an explanatory research type that explains an overview of implementation in an area. The research locus is in Ponorogo Regency. The subjects of this research were selected using purposive key person and snowball procedures. Data collection techniques use interviews, observation and documentation. Researchers carry out data analysis and interpretation by means of data reduction, data presentation, and drawing conclusions. Data quality is obtained through a source triangulation process. The choice of theory in this research uses the implementation theory proposed by Van Horn and Van Meter by looking at the dimensions of program size and objectives, resources, characteristics of implementers, attitudes or dispositions of implementers, communication between implementers, and the economic, social and political environment. The results of this research indicate that there are constraints in resources, attitudes or tendencies of implementers, communication, and the social environment of program recipients. The activity that has the biggest challenge is the effort to increase the income of the recipient family. The researcher's recommendation is to collaborate regarding program funding, carry out a frequency selection process for cadres, and innovate online programs.